The World Organization of Family Doctors Air Health Train the Trainer Program: lessons learned and implications for planetary health education. Issue 1 (January 2023) - McGushin, Alice; de Barros, Enrique Falceto; Floss, Mayara; Mohammad, Yousser; Ndikum, Achiri E; Ngendahayo, Christophe; Oduor, Peter A; Sultana, Sadia; Wong, Rachel; Abelsohn, Alan
Summary: The World Organization of Family Doctors (WONCA) Air Health Train the Trainer Program was a pilot educational programme that focused on a key aspect of planetary health: the intersection of air pollution, human health, and climate change. In this Viewpoint, we—the coordinators of the training programme and some of the most active trainers—briefly describe the programme and discuss implementation successes, challenges, and lessons learned, which relate to the creation and use of training materials appropriate for health professionals in low-income and middle-income countries, strategies to improve the retention of trainers to deliver activities in their communities, and the development of stronger networks and further tools to support trainers. These findings could be applied to future education and training programmes.